2007
DOI: 10.3132/pcrj.2007.00017
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation therapy: an historical review

Abstract: Inhalation has been employed as a method for delivering medications for more than two thousand years, and the benefits of delivering medication directly to the affected site - the lungs - have been understood for more than two hundred years. At the beginning of the Industrial Revolution, physicians were inventing therapies and experimenting with ideas for devices: it was a time of great creativity. However, by the end of the period the scientist and the regulated pharmaceutical industry had emerged and the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
107
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(115 citation statements)
references
References 6 publications
0
107
0
8
Order By: Relevance
“…These inhalers contained a lactosebased drug formulation in small capsules or 'sifters'. For the development of the first device marketed in this period, the Fisons Spinhaler ® (1967), the high dose (20 mg of cromoglycate sodium, which is too high for MDIs) was the main driver [4,10]. Bell et al tested a lactose-based formulation (1:1 with the drug by weight) for this drug too and concluded that the emptying efficiency of the capsule depends very much on the size fraction of the lactose used [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These inhalers contained a lactosebased drug formulation in small capsules or 'sifters'. For the development of the first device marketed in this period, the Fisons Spinhaler ® (1967), the high dose (20 mg of cromoglycate sodium, which is too high for MDIs) was the main driver [4,10]. Bell et al tested a lactose-based formulation (1:1 with the drug by weight) for this drug too and concluded that the emptying efficiency of the capsule depends very much on the size fraction of the lactose used [11].…”
Section: Introductionmentioning
confidence: 99%
“…The history of inhalation therapy has been described before [1][2][3][4]. It dates back to more than 4000 years ago when in India powdered Durata stramonium and Durata ferox, containing potent alkaloids with anticholinergic bronchodilating properties, were smoked after mixing with other compounds such as ginger and pepper [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As requested by the Montreal Protocol in 1987, CFCs eventually were substituted in 1995 by more Benvironmental friendly^hydrofluoroalkane (HFA) gases, which were shown not to disturb the oxygen/ ozone equilibrium in the upper stratosphere (3)(4)(5)(6). It has since been realized that HFA gases are up to 2000-fold more potent than carbon dioxide as greenhouse gases, even so they are estimated to contribute less than 0.1% to global greenhouse gas emission (7,8). pMDIs also suffer from potential difficulties caused by the propellant used (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation became increasingly noted as a therapeutic form in the late-18 th century, first with Philip Stern advocating his own recipe of balsamic vapours in 1764, 3 then John Mudge's invention of a simple pewter inhaler in 1778 (seemingly the first use of the word 'inhaler' by a physician), 4 and finally Thomas Beddoes and Humphry Davy's experiments at the Pneumatic Institute in Bristol in the 1780s and 1790s. 2,5 British (Victorian) physicianinventors were introduced to inhalation anaesthesia from Boston (US America) in 1846-47, which served likewise to normalize perceptions of inhaled medicines and accelerate the exploitation of new materials (e.g. rubber and basic plastics) from the empires.…”
Section: Introductionmentioning
confidence: 99%